Penerapan Pembelajaran Berdiferensiasi menggunakan Media AR untuk Meningkatkan Hasil Belajar Peserta Didik pada Pelajaran IPAS Kelas 4 SDN Banjaran 1 - Sonia Asyrofa; Defi Ratnasari; Maulina Dwi Ristanti; Like Wahyu Anggraini; Afta Fadiana; Farida Nurlaila Zunaidah; Belita Dwi Oktaviani (Jurnal Simki Postgraduate, 2024)
This study aims to improve the learning outcomes of grade 4 students of SD Negeri Banjaran 1 Kediri City in the subject of Science with the material of magnetic force through the application of differentiated learning using AR (Augmented Reality) media. The background is that learning is still based on lectures and assignments which results in students being less enthusiastic in learning. This study uses the Classroom Action Research (CAR) method which consists of two cycles, each covering the planning, implementation, observation, and reflection stages. In the first cycle, learning uses magnetic media and educational videos, while in the second cycle AR media is added. The results showed that the average student score increased from 74.77 in the first cycle with a completion rate of 29.63% to 84.22 in the second cycle with a completion rate of 88.9%. AR media has proven effective in improving understanding of the concept of magnetic force, learning motivation, and student involvement in the learning process.